Solve for x (complex solution)
x=\frac{37y}{6\left(y^{2}-4\right)}
y\neq -2\text{ and }y\neq 2
Solve for x
x=\frac{37y}{6\left(y^{2}-4\right)}
|y|\neq 2
Solve for y
\left\{\begin{matrix}y=\frac{\sqrt{576x^{2}+1369}+37}{12x}\text{; }y=\frac{-\sqrt{576x^{2}+1369}+37}{12x}\text{, }&x\neq 0\\y=0\text{, }&x=0\end{matrix}\right.
Graph
Share
Copied to clipboard
6xy^{2}=24x+37y
Combine 2xy^{2} and 4xy^{2} to get 6xy^{2}.
6xy^{2}-24x=37y
Subtract 24x from both sides.
\left(6y^{2}-24\right)x=37y
Combine all terms containing x.
\frac{\left(6y^{2}-24\right)x}{6y^{2}-24}=\frac{37y}{6y^{2}-24}
Divide both sides by 6y^{2}-24.
x=\frac{37y}{6y^{2}-24}
Dividing by 6y^{2}-24 undoes the multiplication by 6y^{2}-24.
x=\frac{37y}{6\left(y^{2}-4\right)}
Divide 37y by 6y^{2}-24.
6xy^{2}=24x+37y
Combine 2xy^{2} and 4xy^{2} to get 6xy^{2}.
6xy^{2}-24x=37y
Subtract 24x from both sides.
\left(6y^{2}-24\right)x=37y
Combine all terms containing x.
\frac{\left(6y^{2}-24\right)x}{6y^{2}-24}=\frac{37y}{6y^{2}-24}
Divide both sides by 6y^{2}-24.
x=\frac{37y}{6y^{2}-24}
Dividing by 6y^{2}-24 undoes the multiplication by 6y^{2}-24.
x=\frac{37y}{6\left(y^{2}-4\right)}
Divide 37y by 6y^{2}-24.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}